Immigration in a High Unemployment Economy: The Recent Danish Experience - Peder J. Pedersen (Institute for the Study of Labor (IZA), 2000)
The purpose in this paper is to survey the course of immigration into Denmark and research and studies related to the problems encountered in this area. The first part of the paper describes the actual flows of migrants in the most recent decades. The directly job-related part of migration can not be identified precisely. A survey of research results indicate net migration flows towards other OECD countries is sensitive to cyclical indicators and thus mainly labour market related. The paper goes on to survey immigration policy and available evidence regarding the labour market integration of both 1. and 2. generation immigrants. Immigrants and refugees are recorded on average with much higher unemployment and much lower labour market participation than Danish citizens. The status in the late 1990s points to the pressing need for policy initiatives to improve this situation. Finally, the paper summarizes available results regarding the impact on public finances from immigration.
Keywords: J15; J61; 330; Migration history; worker flows; immigration policy; labour market integration; welfare issues; Einwanderung; Internationale Arbeitsmobilität; Migrationspolitik; Ausländische Arbeitskräfte; Arbeitslosigkeit; Öffentlicher Haushalt; Dänemark